Impact of genetic drift, selection and accumulation level on virus adaptation to its host plants. (25th October 2018) - Rousseau, Elsa; Tamisier, Lucie; Fabre, Frederic; Simon, Vincent; Szadkowski, Marion; Bouchez, Olivier; Zanchetta, Catherine; Girardot, Gregory; Mailleret, Ludovic; Grognard, Frederic; Palloix, Alain; Moury, Benoit
SUMMARY : The efficiency of plant major resistance genes is limited by the emergence and spread of resistance‐breaking mutants. Modulation of the evolutionary forces acting on pathogen populations constitutes a promising way to increase the durability of these genes. We studied the effect of four plant traits affecting these evolutionary forces on the rate of resistance breakdown (RB) by a virus. Two of these traits correspond to virus effective population sizes ( N e ) at either plant inoculation or during infection. The third trait corresponds to differential selection exerted by the plant on the virus population. Finally, the fourth trait corresponds to within‐plant virus accumulation (VA). These traits were measured experimentally on Potato virus Y (PVY) inoculated to a set of 84 pepper doubled‐haploid lines, all carrying the same pvr2 3 resistance gene, but having contrasting genetic backgrounds. The lines showed extensive variation for the rate of pvr2 3 RB by PVY and for the four other traits of interest. A generalized linear model showed that three of these four traits, with the exception of N e at inoculation, and several pairwise interactions between them had significant effects on RB. RB increased with increasing values of N e during plant infection or VA. The effect of differential selection was more complex because of a strong interaction with VA. When VA was high, RB increased as the differential selection increased. An opposite relationship between RB and differential selection was observed when VA was low. This study provides a framework to select plants with appropriate virus evolution‐related traits to avoid or delay RB.